Training for Enhancing Tourism Managers' Capacity Through Digital Transformation in Sangiran Tourism Village, Sragen: Pelatihan Peningkatan Kapasitas Pengelola Pariwisata Melalui Transformasi Digital di Desa Wisata Sangiran, Sragen - Sarira, Matius Tinna; Rahmawati, Rahmawati; Nurhayati, Hastuti; Surya Rini, Faradila Anggun (Yayasan Ahmar Cendekia Indonesia, 2024)
This community service program focuses on the need for digital transformation in the management of tourism in Sangiran Tourism Village, aiming to enhance local tourism capabilities. The methodology employed involved hands-on training conducted at the Sangiran Tourism Village Hall on October 11-12, 2024, with 30 participants from various tourism operations. The training encompassed activity planning, implementation, evaluation, and final reporting, emphasizing digital marketing techniques and the use of digital tools for effective tourism promotion. Key findings indicate that participants experienced significant improvement in digital skills, particularly in content management and promotion through social media and QR codes. The evaluation revealed a high satisfaction level, with 86.7% of participants expressing strong approval of the program's effectiveness. This activity concludes that structured community-focused training programs play a crucial role in empowering local tourism practitioners to adapt to digital advancements, ultimately enhancing the competitiveness and sustainability of tourism destinations. Future initiatives should build on these findings to further integrate digital strategies into local tourism development.